The effect of DC bias and noise on the performances of power transformer - Syafruddin Hassan (School of Electrical System Engineering, University Malaysia Perlis, 2014)
This research involved the combination of MATLAB simulation and experimental works. Based on MATLAB program simulation, the results demonstrate that the exciting current becomes much more distort and will incline to half-circle saturation when the DC bias increases from 0.2 T to 1.0 T with the maximum saturation limit of AC magnetic flux density assumed as 2.0 T.